Pharmacokinetic Study of Di-Phenyl-Di-(2,4-Difluobenzohydroxamato)Tin(IV): Novel Metal-Based Complex with Promising Antitumor Potential - Yunlan Li; Zhuyan Gao; Pu Guo; Qingshan Li (Bioinorganic Chemistry and Applications)
Di-phenyl-di-(2,4-difluobenzohydroxamato)tin(IV)(DPDFT), a new metal-based arylhydroxamate antitumor complex, showed high in vivo and in vitro antitumor activity with relative low toxicity, but no data was reported regarding its pharmacokinetics and dependent toxicity. In this paper, a rapid, sensitive, and reproducible HPLC method in vivo using Diamonsil ODS column with a mixture of methanol and phosphoric acid in water (30 : 70, V/V, pH 3.0) as mobile phase was developed and validated for the determination of DPDFT. The plasma was deproteinized with methanol that contained acetanilide as the internal standard (I.S.). The photodiode array detector was set at a wavelength of 228 nm at room temperature and a linear curve over the concentration range 0.1~25 μg·mL-1 (r = 0.9993) was obtained. The method was used to determine the concentration-time profiles for DPDFT in the plasma after single intravenous administration with doses of 5, 10, 15 mg·kg-1 to rats. The pharmacokinetics parameter calculations and modeling were carried out using the 3p97 software. The results showed that the concentration-time curves of DPDFT in rat plasma could be fitted to two-compartment model.